Application of hybrid power flow technique for smart distribution network management - P. Wirasanti (2018)
© 2016 IEEE. to analyze a smart distribution power system network, a conventional power flow technique has to be improved regarding an operation of distributed generation and a new distribution grid concepts. Therefore, an asymmetrical 3-phase 4-wire power flow using hybrid calculation is selected. Originally, the hybrid technique is developed for a decoupling power flow analysis. However, using hybrid technique provides further advantages for smart distribution network operation, which are highlighted in this paper. Firstly, it supports an operation mode of inverter-based distributed generation, i.e. grid forming, grid supporting and grid parallel. Secondly, a voltage regulation regarding optimization process can be simply worked through. It can be done by replacing new hybrid matrix without any modification of power flow algorithm. Lastly, the hybrid technique avoids a mathematical problem in power flow analysis, an inverse matrix problem. This problem can be found in some study of conventional analysis method. To demonstrate an application of hybrid power flow technique, a modified IEEE 34 nodes case study is given.